PENGARUH PROPIOCEPTIVE NEUROMUSCULAR FACILITATION (PNF) HOLD RELAX TERHADAP FLEKSIBILITAS OTOT HAMSTRING PADA REMA - Dinda Rishaldi; Afif Ghufroni; Sukadarwanto (Jurnal Nasional Fisioterapi, 2023)
Background: During the Covid-19 pandemic, people experienced a decrease in daily activities, resulting in shortening of hamstring muscle flexibility. Physiotherapy can help increase the flexibility of the hamstring muscles by providing proprioceptive neuromuscular facilitation (PNF) hold relax. Objective: To determine the effect of PNF hold relax on hamstring muscle flexibility in adolescents. Method: the research method is experimental with a one group pre and post test research design carried out in February-March 2022. The subjects are students at Madrasah Aliah Nawa Kartika, Wonogiri. Using random sampling, 50 subjects were divided into 2 groups, I, numbering 25, and group II, numbering 25. Measuring hamstring muscle flexibility using the active knee extension test (AKET). Results: The results from the treatment group obtained a p value = 0.000. The results in the control group obtained a p value = 0.151. The Man Whitney test between the treatment and control groups resulted in p = 0.000. Conclusion: Providing Proprioceptive Neuromuscular Facilitation (PNF) hold relax has an effect on increasing hamstring muscle flexibility in adolescents.